Regenerative Tourism as a New Paradigm for Island and Marine Destination Sustainability - I Made Murdana; Syech Idrus; Lalu Yulendra (PT. Hafasy Dwi Nawasena, 2026)
Island and marine destinations face an intensifying paradox: the tourism industry that sustains their economies is simultaneously eroding the ecological and social systems on which that economy depends. Conventional sustainable tourism, oriented toward minimizing harm, has proven insufficient to reverse degradation in coral reefs, coastal ecosystems, and small-island communities exposed to overtourism, climate stress, and resource leakage. This article examines regenerative tourism as an emerging paradigm that moves beyond damage limitation toward the active restoration of ecological, cultural, and community vitality in island and marine settings. Using a systematic narrative review of thirty-five peer-reviewed articles published between 2021 and 2026, drawn from international and Indonesian sources, the study synthesizes conceptual foundations, island-specific applications, governance mechanisms, and measurement approaches associated with regenerative tourism. The findings show that regenerative practice depends on living-systems thinking, place-based co-design with local and indigenous communities, circular resource management, and outcome indicators that capture ecological and socio-cultural regeneration rather than visitor volume alone. The article's novelty lies in integrating fragmented conceptual, governance, and indicator-based literature into a single applied framework tailored to island and marine geographies, including Indonesian archipelagic contexts. The article concludes that regenerative tourism offers island and marine destinations a viable pathway toward long-term ecological resilience, community empowerment, and destination competitiveness beyond sustainability.